Coming of age: could obesity-related metabolic complications be treated by targeting senescent cells? - Kasperova, Barbora Judita; Cinkajzlova, Anna; Horvath, Ludek; Svoboda, Petr; Haluzik, Martin; Stemberkova Hubackova, Sona (Frontiers in Cell and Developmental Biology, 2025)
Aging is characterized by gradual deterioration of organ or tissue function and its ability to maintain homeostasis of the different physiological processes. This leads to the development of structural and functional alterations accompanied by an increased risk for diverse pathologies. Cellular senescence is a controlled biological process that could contribute to the development of many age-related diseases and related metabolic dysfunctions. Two major chronic diseases associated with premature accumulation of senescent cells that impose an enormous burden on global health systems are obesity and type 2 diabetes mellitus with its related complications. The purpose of this review is to highlight the links between aging, obesity, and type 2 diabetes mellitus, focusing on the role of cellular senescence in disease development and progression. Additionally, this review will discuss the potential of targeting cellular senescence as a promising therapeutic strategy for managing these interrelated diseases, therefore offering a novel approach to prevention and treatment.